Provider trends in paediatric and adult transfusion reaction reporting. Issue 3 (7th February 2019) - Vossoughi, Sarah; Parker‐Jones, Sylvia; Schwartz, Joseph; Stotler, Brie
Abstract : Background and Objectives: Passive transfusion reaction reporting systems fail to capture a significant number of reactions, and no data exist on provider reporting trends. The aim of this study was to describe transfusion reaction reporting patterns by adult and paediatric providers. Materials and Methods: This is a multihospital study on transfusion reaction reporting over a 7‐year period. Reports were categorized according to transfusion location and assigned to either a transfusion reaction or nonreaction group according to Centers for Disease Control imputability guidelines. Included in the reaction group (RXN) were definite, probable or possible reaction categories; with the remainder assigned as nonreactions (NORXN). Rates were calculated per 100, 000 components transfused using chi‐square comparison. Results: There were 1092 reports generated from 363 437 transfusions; 230 reports from 69 311 paediatric and 862 reports from 294 126 adult treatment areas. The reporting rate per 100 000 components transfused was 332 for paediatric and 293 for adult ( P  = 0·09). The per 100 000 components transfused rates were as follows: 237 for paediatric and 169 for adult ( P  < 0·01) in the RXN group; with 95 paediatric and 124 adult rates in the NORXN group ( P  = 0·04). Conclusion: The total number of reports generated by paediatric and adult providers was not significantly different, suggesting that both provider groups engage the passive reporting system equally. However, paediatric providers reported more true reactions compared to adult providers. Robust hemovigilance systems will further the understanding of these trends and may aid in the development of targeted provider education programmes.